Towards a novel cache replacement strategy for Named Data Networking based on Software Defined Networking. (February 2018) - Kalghoum, Anwar; Gammar, Sonia Mettali; Saidane, Leila Azouz
Abstract: The Information Centric Networking (ICN) approach proposes to rebuild the Internet communication model and to focus entirely on the data content. Although the Named Data Networking (NDN) architecture is considered as one of the most credible ICN architectures, it does not have an effective cache replacement system. Software Defined Networking (SDN) is an architecture where the control plan is completely decoupled from the data plane. In fact, with the steady growth of existing network infrastructures, we take advantage of the SDN to enhance the caching in the NDN architecture. In this paper, we introduce a Named Data Networking Cache replacement approach based on SDN, that we called NC-SDN. Thus, our proposal relies on data popularity calculation performed by the switches to define a cache replacement strategy. Through experimental tests, we evaluated the performance of our solution, and we compared it to the NDN equipped with different cache replacement policy.